(untitled) (The Pakistan Development Review, 2005)
This paper, begins with a discussion of the well-known issues involved in defining and measuring total factor productivity (TFP) and its contribution to growth (as well as the possible contribution of growth to productivity), the economic theory underpinning productivity, and policies that impact on and influence changes in productivity. It is followed by, first, a selective discussion of the studies on cross-country variation in productivity levels and growth, and then the experience of South Asia and China in a comparative perspective across the region and across the developing world. The share of South Asia in global GDP and its growth has remained stagnant since the early nineties. Disturbingly, except India, the rest of South Asia experienced a decline in TFP growth between 1989-95 and 1995-2003. The paper concludes that for achieving sustained productivity growth, well-functioning social and economic institutions are important, since through their incentive structure they influence, labour force participation, savings and accumulation of human and physical capital, risk-taking and innovation as well as efficiency of resource allocation. Public policies, particularly macro-economic, foreign trade and investment policies, matter a great deal.